Midterm Prognosis of Sexagenary Patients after Transcatheter Device Closure of Atrial Septal Defects: a Single-Chinese Center Experience - Sun,Kai-Peng (2022)
Abstract Introduction: The objective of this study is to evaluate the efficacy and midterm prognosis of transcatheter device closure of atrial septal defects (ASDs) in sexagenary patients in China. Methods: Forty-six sexagenary patients who underwent transcatheter device closure of ASDs in our hospital were included in this study. The patients’ preoperative and postoperative clinical symptoms, echocardiographic results, and quality of life were investigated and analyzed. Results: Of the 46 sexagenary patients who participated in the study, 40 completed the study. After ASD closure, the clinical symptoms of the patients significantly improved, and the number of patients with dyspnea and palpitations significantly decreased after the operation. According to the echocardiographic results, few patients had a tiny residual shunt after closure, but the shunt disappeared completely at the three-month follow-up. The size of the right ventricular cavity was significantly smaller postoperatively compared with preoperatively. Regarding the patients’ quality of life, their feedback in all dimensions of the 36-Item Short-Form Health Survey (or SF-36) was significantly improved at the three-month follow-up, and it remained improved at the one-year follow-up. Conclusion: The clinical outcomes and subjective quality of life of sexagenary patients with ASDs improved significantly after transcatheter device closure of ASDs. Therefore, we believe that for sexagenary patients with ASDs, transcatheter device closure is a favorable treatment.